174 An ex vivo tumoroid model of fresh patient tumors (3D-ACT) to assess efficacy of cellular therapy in immuno-oncology. (9th November 2020) - Iwanowycz, Stephen; Ehrhart, Jared; Pabon, Mibel; Pastoor, Tina; Kreahling, Jenny; Altiok, Soner
Abstract : Background: Adoptive T cell therapy (ACT) strategies have achieved substantial advances in the treatment of malignant tumors. Some of the unique challenges posed to ACT by solid tumors include locating target cells, as well as entering and surviving the complex tumor microenvironment. To develop better ACT applications and identify combination therapies to enhance tumor cell killing efficacy of ACT it is imperative to develop preclinical platforms that recapitulate the complexity of patient tumor microenvironment (TME). The goal of this study was to develop an integrated confocal-based high-throughput, high-content real time imaging platform to assess immunogenic tumor cell killing (TCK) activity of ACT applications such as CAR-T and TCR using fresh patient tumor samples. Methods: All patient tumor samples were obtained with patient consent and relevant IRB approval. For the confocal imaging platform, unpropagated 3D tumoroids with intact TME measuring 150 micron in size were prepared from fresh tumor samples of renal cell carcinoma (RCC), colorectal carcinoma (CRC) and non-small cell lung cancer (NSCLC) using proprietary technology developed at Nilogen Oncosystems. Engineered T-cells were labeled with different fluorescent cell tracker dyes to monitor cell migration and locations within tumoroids by confocal analysis. Comprehensive flow cytometry analysis was performed to corroborate confocal imaging findings from TCK and multiplex cytokine release assays used to assess changes in the TME. Results: Our studies demonstrated that the confocal-based high-content real time imaging platform described here, combined with a custom image analysis algorithm, allowed for monitoring of treatment-mediated tumor cell killing with structural and functional analysis of engineered T-cells in intact 3D tumoroids. The penetration rate of CAR-T and TCR cells into tumoroids as well as associated tumor cell death varied significantly between different tumor types. Flow cytometry analysis allowed for monitoring of the activation status and viability of engineered T-cells, and treatment-mediated changes in tumor resident immune cell populations. Conclusions: Our data indicated that the immunosuppressive tumor microenvironment may have implications for the application of ACT. Use of the ex vivo platform described here (3D-ACT) may aid in the validation of combinatorial therapies that block or deplete suppressive factors present within the TME, allowing these therapies to overcome mechanisms associated with dysfunction in CAR-T and TCR cell applications. Ethics Approval: The study was approved by Chesapeake IRB Pro00014313.